The risk management approach to monetary policy, nonlinearity and aggressiveness: the case of the US Fed - Diego Moccero; Jean-Yves Gnabo (European Central Bank (ECB), 2015)
We estimate regime switching models where the strength of the response of monetary policy to macroeconomic conditions depends on the level of risk associated with the inflation outlook and risk in financial markets. Using quarterly data for the Greenspan period we find that: i) risk in the inflation outlook and volatility in financial markets are a powerful driver of monetary policy regime changes in the U.S.; ii) the response of the US Fed to the inflation outlook is invariant across policy regimes; iii) however, in periods of high economic risk, monetary policy tends to respond more aggressively to the output gap and the degree of inertia tends to be lower than in normal circumstances; and iv) the US Fed is estimated to have responded aggressively to the output gap in the late 1980s and begging of the 1990s, and in the late 1990s and early 2000s.
Keywords: C24; C51; E52; 330; aggressiveness; monetary policy; risk management; smooth-transition regression model; US Fed